Architectural model from the information view to support interoperability of software tools that support software process improvement (2016)
(Eng) Diverse software tools that support the software process improvement (SPI) not interoperate between them, that is to say, the exchange of information between the different tools is deficient, making it difficult to sequence and automatic re-use of information of SPI initiatives. In this article we present an architectural model from the information view to support the interoperability of software tools that support the stages of diagnosing the process and formulating improvements. The model establishes architecture that describes the type of information that can be exchanged these tools, as well as the structure of the data, their possible values, its semantics, and the restrictions imposed on the use and interpretation of such information. The architectural model is composed of a set of schemas, raised in conceptual form, which can be used by organizations that wish to develop software tools to interoperate, which provide support in a comprehensive way to diagnosing the process and formulating improvements of the SPI cycle. These schemas were evaluated using the qualitative method Focus Group.